Pearson correlation coefficient of the student perception and challenges towards open and distance learning during COVID-19 / Wan Noor Hayatie Wan Abdul Aziz ...[et al.] - Wan Abdul Aziz, Wan Noor Hayatie; Abu Hasan, Nurhasniza Idham; Mohammad Hamzah, Mohd Hafiz; Wan Abdul Aziz, Rossidah (UiTM Press, 2020)
COVID-19 pandemic has a huge change in worldwide education. Previous face to face method of learning have been change to open and distance learning. This study investigated students’ perceptions and challenge of Open and Distance Learning (ODL) during COVID-19 in Institution of Higher Learning (IHL). Data were collected from 141 online students of IHL using Google Form. The independent sample t-test used to compare the mean of student perception and students challenges among socio-demographic. Meanwhile the Pearson correlation coefficient is also used to identify the relationship between the overall score of student perception and student challenges. As a result, the research revealed that there are significant moderate negative associations between students’ perception and students challenge.